The emerging role of targeting cancer metabolism for cancer therapy - Pegah Farhadi; Reza Yarani; Sadat Dokaneheifard; Kamran Mansouri (Tumor Biology)
Glucose, as the main consuming nutrient of the body, faces different destinies in cancer cells. Glycolysis, oxidative phosphorylation, and pentose phosphate pathways produce different glucose-derived metabolites and thus affect cells’ bioenergetics differently. Tumor cells’ dependency to aerobic glycolysis and other cancer-specific metabolism changes are known as the cancer hallmarks, distinct cancer cells from normal cells. Therefore, these tumor-specific characteristics receive the limelight as targets for cancer therapy. Glutamine, serine, and fatty acid oxidation together with 5-lipoxygenase are main pathways that have attracted lots of attention for cancer therapy. In this review, we not only discuss different tumor metabolism aspects but also discuss the metabolism roles in the promotion of cancer cells at different stages and their difference with normal cells. Besides, we dissect the inhibitors potential in blocking the main metabolic pathways to introduce the effective and non-effective inhibitors in the field.